Implications of fit customization in the apparel industry: an analytical study - Zhenzhen, Huang; Faridah, Sahari (Emerald Group Publishing Ltd., 2025)
Purpose Numerous studies have examined technologies and influencing factors related to garment fit to enhance the implementation of fit customization (FC). Nevertheless, achieving optimal fit remains a complex challenge within the apparel industry. This study aims to explore how advanced technologies are used in the implementation of FC in apparel industry, and to identify the key factors influencing fit from the perspective of clothing industry professionals, with the aim of improving customization practices.